The Advances in Utilizing Right Ventricular Function as a Predictor of Peripartum Cardiomyopathy Recovery: A Single Centre Prospective Cohort Study - Akbar MR; Sakasasmita S; Achmad C; Dewi TI; Hasan M; Prameswari HS (International Journal of General Medicine, 2025)
Mohammad Rizki Akbar,* Sylvie Sakasasmita,* Chaerul Achmad, Triwedya Indra Dewi, Melawati Hasan, Hawani Sasmaya Prameswari* Department of Cardiology and Vascular Medicine/ Dr. Hasan Sadikin General Hospital, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia*These authors contributed equally to this workCorrespondence: Mohammad Rizki Akbar, Department of Cardiology and Vascular Medicine, Universitas Padjadjaran, Pasteur 38, Sukajadi, Bandung, West Java, 40161, Indonesia, Tel +6281221040265, Email m.r.akbar@unpad.ac.idIntroduction: Peripartum cardiomyopathy (PPCM) is a pregnancy related cardiomyopathy with a high potential for recovery. One of the contemporary predictors studied in cardiomyopathy is right ventricular (RV) function during initial presentation.Purpose: This study aimed to determine the role of RV systolic function based on the various RV function parameters by two-dimensional transthoracic echocardiography (2DE) to predict PPCM recovery within 6 months of follow-up and identify the most accurate parameter among them.Patients and Methods: This was a prospective cohort study that include all patients registered in the “Long Term Registry on Patients with Peripartum Cardiomyopathy” at Dr. Hasan Sadikin General Hospital Indonesia during period of September 2014 until December 2022. Right ventricular systolic dysfunction was defined as abnormal value in one or more parameter(s), including tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), S’, right ventricular free wall longitudinal strain (RVFWLS) and right ventricular global longitudinal strain (RVGLS). Left ventricular ejection fraction was measured on initial examination and after 6-month follow up to define recovery.Results: A total of 95 patients were included in this study. There were 33 patients (34.7%) with reduced initial RV systolic function. Sixty-four patients (67.4%) recovered within 6 months follow up. The recovery rate of patients with initial RV systolic dysfunction is lower than patients with normal RV systolic function (51.5% vs 75.8%, p = 0.016). This study showed that initial RV systolic dysfunction can predict poor LV function recovery in PPCM patients (OR 0.340; 95% CI:0.120– 0.959; p = 0.041). Among all RV function parameters, only FAC (OR 1.076; 95% CI:1.003– 1.154; p = 0.040)) and RVGLS (OR 0.768; 95% CI: 0.595– 0.991; p = 0.042) emerged as independent predictors of PPCM recovery.Conclusion: Right ventricular function in terms of FAC and/or RVGLS at initial diagnosis can be used as a predictor for PPCM recovery at 6 months follow-up.Keywords: FAC, PPCM, right ventricle, RVGLS